2010
DOI: 10.1111/j.1471-1842.2009.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

An information behaviour investigation of the community pharmacists in Greece for developing library and information services

Abstract: Background and objectives: Community pharmacists require a constant provision of high quality information for updating their knowledge and improving their practices and skills. The development of library and information services for the pharmacists in a meaningful way should take into consideration their information behaviour and needs. This study is an investigation of the information behaviour of community pharmacists in Greece, as well as their perceptions regarding the contribution of library and informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In relation to other enablers training in available information resources , a dequate time to share information and o rganisational structure facilitates sharing were also noted by the participants. These findings are in par with previous research that has similarly identified lack of time of pharmacists as a barrier to accessing information (Kostagiolas et al ., 2010). If we consider these results in conjunction with the earlier information sources results, on the basis of the frequency of using forums/meetings/seminars/working groups as well as c orporate network communities , where, overall below average values were obtained, perhaps, the provision of increased opportunities for information sharing through forums, seminars, meetings and working groups could further enhance information sharing, through fostering communities of practice where individuals to act “as resources to each other, exchanging information, making sense of situations, sharing new tricks and new ideas” (Wenger, 1998, p. 47).…”
Section: Discussionsupporting
confidence: 81%
“…In relation to other enablers training in available information resources , a dequate time to share information and o rganisational structure facilitates sharing were also noted by the participants. These findings are in par with previous research that has similarly identified lack of time of pharmacists as a barrier to accessing information (Kostagiolas et al ., 2010). If we consider these results in conjunction with the earlier information sources results, on the basis of the frequency of using forums/meetings/seminars/working groups as well as c orporate network communities , where, overall below average values were obtained, perhaps, the provision of increased opportunities for information sharing through forums, seminars, meetings and working groups could further enhance information sharing, through fostering communities of practice where individuals to act “as resources to each other, exchanging information, making sense of situations, sharing new tricks and new ideas” (Wenger, 1998, p. 47).…”
Section: Discussionsupporting
confidence: 81%
“…This was echoed in a survey-based study conducted by Kostagiolas et al . [29] in Greece revealing that pharmacists perceived a significant contribution of their role to dealing with health-care prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the variation in content, speakers, sponsors, and level of topics limit their usefulness and less reliable compared to other sources of information 2, 9-11 . Community pharmacists are efficiently looked upon to provide accurate, up to-date, reliable, unbiased or two sided information in the fast-paced environment of community pharmacy. Pharmacists therefore need access to comprehensive information sources on medication 12 . Generally, there are three categories of drug information 2 .…”
mentioning
confidence: 99%